100 Robotic Distal Pancreatectomies: The Future at Hand. Issue 8 (August 2020) - Rosemurgy, Alexander S.; Luberice, Kenneth; Krill, Emily; Castro, Miguel; Espineira, Gabriel Rivera; Sucandy, Iswanto; Ross, Sharona
Introduction: This study was undertaken to examine 100 consecutive robotic distal pancreatectomies with splenectomies, and to compare our outcomes to predicted outcomes as calculated using the American college of surgeons national surgical quality improvement program (ACS NSQIP) Surgical Risk Calculator and to the outcomes contained within NSQIP. Methods: Outcomes were compared with predicted outcomes, calculated using the ACS NSQIP Surgical Risk Calculator, and with outcomes documented in NSQIP for distal pancreatectomy. For illustrative purposes, data are presented as median (mean ± SD). Results: Patients who underwent robotic distal pancreatectomy were of age 67 (63 ± 13.4) years with a BMI of 29 (29 ± 6.3) kg/m 2, with 49% being women. Operative duration was 242 (265 ± 112.2) minutes and estimated blood loss was 110 (211 ± 233.9) mL. Predicted outcomes were similar to those reported in NSQIP. Our actual outcomes were significantly superior to the predicted outcomes for serious complication, any complication, surgical site infection, sepsis, and length of stay. Compared to NSQIP outcomes, our actual outcomes for serious complication, any complication, surgical site infection, sepsis, and delayed gastric emptying were significantly superior. Twelve percent of operations were converted to "open." There were 3 deaths within 30 days, similar to predicted outcomes. Deaths were due to sepsis (2) and respiratory failure (1). Conclusion: Our patients' predicted outcomes were the same as national outcomes; our patients were not a select group. However, their actual outcomes were like or significantly superior than those predicted by NSQIP or reported in NSQIP. We believe that the robot has the future of distal pancreatectomy with or without splenectomy.